A New Phenanthroline Ligand and the Spontaneous Resolution of its Homoleptic Copper(I) Complex. Issue 47 (29th September 2020) - Appleton, Jordan L.; Silber, Vincent; Karmazin, Lydia; Bailly, Corinne; Chambron, Jean‐Claude; Weiss, Jean; Ruppert, Romain
Abstract : During the synthesis of 1, 10‐phenanthroline derivatives sterically hindered in the 2 and/or 9 positions, serendipity led to the discovery of a new substitution pattern on phenanthroline with good and reproducible yields. When toluene was used as a solvent and the aryl‐lithio reagents generated with tBuLi, after a first substitution at the 2 position, a benzyl substituent was regioselectively introduced at the 7 position. It is proposed that the benzyllithium reagent is formed by reaction with the solvent and that the steric hindrance on the intermediates controls the nucleophilic addition. Among the complexes prepared (Pd(II), Cu(I)) with these new ligands, a chiral copper(I) complex exhibits spontaneous resolution in the solid state. Abstract : A benzyl substituent was regioselectively introduced at the 7 position after a first substitution at the 2 position of 1, 10‐phenanthroline, by using aryl‐lithio reagents generated with tert ‐butyllithium in toluene. Among the complexes prepared (Pd(II), Cu(I)) with these new ligands, a chiral copper(I) complex exhibits spontaneous resolution in the solid state.